A interface prosódia / pragmática nas expressões faciais das emoções dos surdos - CARDOSO, Edinalva Cardoso e (2019)
We had as main objective to understand the facial expressions of basic emotions of the deaf, pondering the interface prosody/pragmatic. Particularly, we identified the visual prosody of six (6) basic emotions (happiness, fear, disgust, surprise, anger and sadness). In addition, we observed the prosodic aspect of expressiveness of emotion in Brazilian Sign Language (Libras). We assume that deaf individuals would find barriers to expressing basic emotions because they are immersed in listening environment. We take as a basis the prosody of the facial expressions of the emotions in the communicative contexts treated by Correia (2014); Page 2 Bodolay (2009) and Theory of the Acts of Speech of Austin and Searle (1981). Three (3) bilingual deaf people in Libras / Português, high school students, enrolled in the public school system of the city of Abaetetuba / PA, aged between 18 and 24, participated in this study. For four weeks, the participants produced in Pounds 4 tasks in the following order: a) textual production in Pounds of fables; b) production in Portuguese and exposition in Pounds of spontaneous phrases; c) reading and presentation in Pounds of the short stories "If a cat is" (Cipis, 2009); "Certainly many doubts" (Silva et al, 2004); "The monosyllabic boy" (Goltcher, 2006); d) production in Portuguese and exposition in Pounds Sterling. In order to verify the realization of facial expressions prosodic (anger, joy, sadness, fear, disgust and surprise). We used the FACS (Facial Affect Coding System) developed by Ekman, Friesen, and José C. Hager in 2002. The deaf held five (5) basic facial expressions of emotion: joy, sadness, anger, fear and amazement, at a ratio of R- 5, T-2 and M- 2, in accordance with the contexts of interaction, in which the explanatory of the tasks had emotional situations commensurate to prosodic expressions. In addition, have not yielded the prosody of the expressiveness of the emotion disgust. We noticed that the junction of the context (pragmatic) and prosody (facial expressions) are essential for the proper development of communicative and which contribute to understand linguistic phenomena in the language of signs, in the case in Libras.